PCR amplification of ITS rDNA from rust teliospores collected on southwestern rangeland from 1907 to 1995 - Craig Liddell; Kathy Onsurez Waugh (Fungal Genetics Reports, 1996)
Evidence of evolutionary change in the rust, Puccinia grindeliae, populations in New Mexico and Arizona, is revealed by use of PCR amplified ITS regions of rDNA. Polymorphic ITS5 - ITS2 fragments were found both within a single community and among geographically and temporally separated collections. These results provide evidence for genetic heterogeneity, possibly resulting from recent evolutionary change in reproductive strategy from clonal to sexual.